THE INFLUENCE OF ORGANIZATIONAL CULTURE, EMPLOYEE EMPOWERMENT AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENTS - Isya Wahyudin; Ismu Hadjar; Nancy Yusnita (Agricultural Socio-Economics Journal, 2021)
Organizational commitment is the willingness of someone who is in an organization to obey, respect and live the values set by the organization, and the main purpose of organizational commitment is to foster a loyal attitude to the organization. This study aims to empirically reveal the influence of organizational culture, employee empowerment and job satisfaction on organizational commitment with the object of employee research at CV. Tirta Usaha Bogor and a total sample of 140 respondents using path analysis. CV. Tirta Usaha Bogor is a distribution company for bottled water products with Aqua and Vit brands. The results show that organizational culture directly affects organizational commitment with a coefficient of 0.31, employee empowerment directly affects organizational commitment with a coefficient of 0.32, and job decision directly affects organizational commitment with a coefficient of 0.19. Commitment to the organization that occurs at CV. Tirta Usaha Bogor is currently strong enough, even with the conditions of organizational culture, empowerment and job satisfaction that are in the good enough category can create commitment to the organization that is good enough to good. If things related to organizational culture, employee empowerment and job satisfaction can be improved, it will create a strong commitment to the organization in each employee.